What works to protect, promote and support breastfeeding on a large scale: A review of reviews - Tomori, Cecília; Hernández-Cordero, Sonia; Busath, Natalie; Menon, Purnima; Pérez-Escamilla, Rafael (Wiley, 2022)
Globally women continue to face substantial barriers to breastfeeding. The 2016 Lancet Breastfeeding Series identified key barriers and reviewed effective interventions that address them. The present study updates the evidence base since 2016 using a review of reviews approach. Searches were implemented using the Epistomenikos database. One hundred and fifteen reviews of interventions were identified and assessed for quality and risk of bias. Over half of reviews (53%) were high- or moderate quality, with the remaining low or critically low quality due to weaknesses in assessment of bias. A large portion of studies addressed high-income and upper-middle income settings, (41%), and a majority (63%) addressed health systems, followed by community and family settings (39%). Findings from reviews continue to strengthen the evidence base for effective interventions that improve breastfeeding outcomes across all levels of the social-ecological model, including supportive workplace policies; implementation of the Baby-Friendly Hospital Initiative, skin to skin care, kangaroo mother care, and cup feeding in health settings; and the importance of continuity of care and support in community and family settings, via home visits delivered by CHWs, supported by fathers', grandmothers' and community involvement. Studies disproportionately focus on health systems in high income and upper-middle income settings. There is insufficient attention to policy and structural interventions, the workplace and there is a need for rigorous assessment of multilevel interventions. Evidence from the past 5 years demonstrates the need to build on well-established knowledge to scale up breastfeeding protection, promotion and support programmes.